Criminal sanctions for insider trading: Comparison with Singapore - Ainul Azizah (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Insider trading is one of the crimes in the capital market that causes a lot of material loss to the victim. Such a large loss has caused fears of investors to trade on the capital market in Indonesia. For this reason, the government is trying to prevent insider trading, the government has made a Capital Market Law, but this is not enough. For this reason, policies need to be made relating to criminal sanctions for perpretators insider trading in the future. The research method used is the normative legal research method. With a conceptual approach, comparison and Law. The legal issues that will be examined are the legal and philosophical foundations of criminal sanctions for perpetrators insider trading and criminal law policies relating to criminal sanctions for perpetrators insider trading in the future? The result is a legal basis for criminal sanctions for perpetrators insider trading is to provide a deterrent effect to the perpetrators so that it does not happen again and protect the public from insider trading. Policies relating to criminal sanctions for perpetrators insider trading are the use of schikking in resolving insider trading and by using non-litigation methods.Keyword : criminal sanctions; insider trading; comparison.